Pengendalian Kualitas Produk Unit Plastik Woven Bag Dalam Upaya Mengendalikan Tingkat Kecacatan Produk Dengan Bantuan Statistical Process Control (SPC): Studi Kasus PT. Dasaplast Nusantara - Zumrotul Khamidah, Sugoro Bhakti Sutono (Journal of Industrial Engineering and Technology, 2021)
Quality is an achievement or assessment of an item or service from various factors based on the conformity of the specifications desired by the manufacturer. Good product quality can provide confidence for customers to order or cooperate in business so that it can improve the company's position against its competitors. PT. Dasaplast Nusantara is a company producing plastic woven bags or plastic sacks, the raw materials used in the manufacture of products have a high enough price, so the company must really maintain the quality of the product so that the company does not suffer a large enough loss. Thus, in this study, quality control was carried out using the Statistical Process Control (SPC) method which aims to control the level of product defects in the plastic woven bag unit. By using the SPC method, the company's defect rate is 12%, which means that the production capability is not good